1999
DOI: 10.1021/cm980636d
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Porphyrin Containing Zirconium Phosphonate Langmuir−Blodgett Films

Abstract: The substituted tetraphenylporphyrins palladium 5,10,15,20-tetrakis(2′,3′,5′,6′-tetrafluorophenyl-4′-octadecyloxyphosphonic acid)porphyrin ( 16) and palladium 5,10,15-tris(2′,6′dichlorophenyl)-20-(2′,3′,5′,6′-tetrafluorophenyl-4′-octadecyloxyphosphonic acid)porphyrin ( 17) have been studied as Langmuir monolayers and as zirconium phosphonate Langmuir-Blodgett (LB) films. Using a three-step deposition technique, symmetric and alternating zirconium phosphonate bilayers and multilayers were prepared. In these fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 42 publications
2
55
0
Order By: Relevance
“…Consistent with earlier reports [14][15][16][17], we have recently found that stable multilayer films based on a rigid 5,15-functionalized porphyrin bis-phosphonates and related supramolecular assemblies can be prepared on indium-tin oxide (ITO) coated glass slides [18,19]. This method involves the formation of a zirconium layer on the conductive surface and sequential adsorption of porphyrin bisphosphonates and ZrOCl 2 providing multilayer films.…”
Section: Introductionsupporting
confidence: 83%
“…Consistent with earlier reports [14][15][16][17], we have recently found that stable multilayer films based on a rigid 5,15-functionalized porphyrin bis-phosphonates and related supramolecular assemblies can be prepared on indium-tin oxide (ITO) coated glass slides [18,19]. This method involves the formation of a zirconium layer on the conductive surface and sequential adsorption of porphyrin bisphosphonates and ZrOCl 2 providing multilayer films.…”
Section: Introductionsupporting
confidence: 83%
“…A number of studies demonstrated the formation of zirconium phosphonate films on various surfaces because of potential applications in catalysis, sensing, electronics, protein immobilization, and separations (Lee et al, 1988; Putvinski et al, 1990; Hong, Sackett, & Mallouk, 1991; Byrd, Pike, & Talham, 1993; Frey, Hanken, & Corn, 1993; Byrd et al, 1994; Nixon et al, 1999; Clearfield et al, 2000; Kohli & Blanchard, 2000; Kumar & Chaudhari, 2000; Benitez et al, 2002; Nonglaton et al, 2004; Mazur, Krysinski, & Blanchard, 2005). Zr(IV) binds strongly to phosphonate monolayers due to metal ion‐ligand crosslinking (Zr(IV) ions coordinate to more than one phosphonate molecule), (Byrd, Pike, & Talham, 1993; Byrd et al, 1994) and multilayer Zr(IV) phosphonate films can also be prepared (Nixon et al, 1999; Clearfield et al, 2000; Kohli & Blanchard, 2000). With regard to phosphopeptide enrichment, Zhou and co‐workers used zirconium phosphonate monolayers immobilized on porous silicon as phosphopeptide affinity probes for MALDI‐TOF‐MS (Zhou et al, 2006).…”
Section: New Platforms Aimed To Simplify the Enrichment Proceduresmentioning
confidence: 99%
“…Indeed, the zirconium phosphonates reported in literatures are a class of versatile materials with promising applications such as catalyst supporters, heavy metal sorbents, as well as proton-conducting materials1819202122. However, there are two key hurdles for the further development of zirconium phosphonate MOFs.…”
mentioning
confidence: 99%
“…Compared to zirconium carboxylate MOFs, tetravalent zirconium phosphonates are proposed to possess elevated stabilities owing to the higher p K a values of the phosphonate ligands 17 . Indeed, the zirconium phosphonates reported in literatures are a class of versatile materials with promising applications such as catalyst supporters, heavy metal sorbents, as well as proton-conducting materials 18 19 20 21 22 . However, there are two key hurdles for the further development of zirconium phosphonate MOFs.…”
mentioning
confidence: 99%